Secondary alveolar bone graft in incomplete unilateral pre-foramen fissure: case report (Research, Society and Development, 2022)
Cleft lip and palate is one of the most common facial deformities. During embryonic life, non-fusion of the maxillary and medial nasal plaques leads to cleft lip and palate. Fissures can produce a range of dental problems in terms of number, size, shape, and position, related to deciduous or permanent dentition. Besides this, the teeth most affected are those located in the fissure area. There are numerous treatment protocols, which, despite the lack of a consensus, start as soon as the child is born, going into adulthood, seeking functional and aesthetic rehabilitation. The surgical phases, lip repair, nasal repair, palatoplasty and alveolar bone grafting, are performed according to age. As for the bone graft, the most used option is the secondary graft, with the autogenous one being the most available. Thus, the objective of this work is to present a clinical case of secondary alveolar bone grafting in a 10-year-old female patient with an incomplete unilateral pre-foramen cleft.